Epithelium-dependent effect of L-glutamate on airways: involvement of prostaglandins - Apostolia A. Hatziefthimiou; Konstantinos I. Gourgoulianis; Paschalis-Adam Molyvdas (Mediators of Inflammation)
We investigated the effect of the excitatory amino acid (EAA) receptor agonists L-glutamate, N-methyl-D-aspartate (NMDA), (RS)-a-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) and kainic acid on KCl-induced contractions of rabbit tracheal smooth muscle, as well as the role of epithelium and endogenously produced nitric oxide and prostaglandins on these responses. L-Glutamate decreased KCl-induced contractions up to 30%. This effect was attenuated by epithelium removal, tetrodotoxin, methylene blue and indomethacin but not by NG-nitro-L-arginine methyl ester. While NMDA, AMPA and kainic acid had no effect, the combination of NMDA + kainic acid decreased KCl-induced contractions. These results suggest that, in rabbit trachea, L-glutamate has, at least in part, an epithelium-dependent effect mediated via prostaglandin formation and that the EAA receptors involved are nonclassical.